Drug resistant integrase mutants cause aberrant HIV integrations. Issue 1 (December 2016) - Varadarajan, Janani; McWilliams, Mary; Mott, Bryan; Thomas, Craig; Smith, Steven; Hughes, Stephen
Abstract Background HIV-1 integrase is the target for three FDA-approved drugs, raltegravir, elvitegravir, and dolutegravir. All three drugs bind at the active site of integrase and block the strand transfer step of integration. We previously showed that sub-optimal doses of the anti-HIV drug raltegravir can cause aberrant HIV integrations that are accompanied by a variety of deletions, duplications, insertions and inversions of the adjacent host sequences. Results We show here that a second drug, elvitegravir, also causes similar aberrant integrations. More importantly, we show that at least two of the three clinically relevant drug resistant integrase mutants we tested, N155H and G140S/Q148H, which reduce the enzymatic activity of integrase, can cause the same sorts of aberrant integrations, even in the absence of drugs. In addition, these drug resistant mutants have an elevated IC50 for anti-integrase drugs, and concentrations of the drugs that would be optimal against the WT virus are suboptimal for the mutants. Conclusions We previously showed that suboptimal doses of a drug that binds to the HIV enzyme integrase and blocks the integration of a DNA copy of the viral genome into host DNA can cause aberrant integrations that involve rearrangements of the host DNA. We show here that suboptimal doses of a second anti-integrase drug can cause similar aberrant integrations. We also show that drug-resistance mutations in HIV integrase can also cause aberrant integrations, even in the absence of an anti-integrase drug. HIV DNA integrations in the oncogenes BACH2 and MKL2 that do not involve rearrangements of the viral or host DNA can stimulate the proliferation of infected cells. Based on what is known about the association of DNA rearrangements and the activation of oncogenes in human tumors, it is possible that some of the deletions, duplications, insertions, and inversions of the host DNA that accompany aberrant HIV DNA integrations could increase the chances that HIV integrations could lead to the development of a tumor.